Performance Analysis of New Main Protection Scheme for Rotor Winding of Variable Speed Pumped Storage Units - Jianing BAI; Lin GUI; Miao LIU; Yanjun LI; Chenguang GAO; Tianzhi CAO; Yian YAN (Zhongguo dianli)
The operation of Fengning variable speed pumped storage units has made the main protection scheme of the rotor winding a hot issue. The multi-loop analysis method is used to simulate all possible internal faults in the rotor winding of the 12 kW AC excitation dynamic simulation electrical machine manufactured by Xiangtan Electrical Manufacturing Factory. Based on this, the performance of a new main protection scheme for the rotor winding based on stator branch harmonic circulation is analyzed, and the types of faults that the main protection scheme for the new rotor winding cannot operate are further clarified and corresponding improvement measures are proposed, which can provide a reference for the stable operation of the variable speed pumped storage units in the future domestic demonstration projects in China.